2007
DOI: 10.1111/j.1365-2249.2007.03492.x
|View full text |Cite
|
Sign up to set email alerts
|

Serotonin modulates the cytokine network in the lung: involvement of prostaglandin E2

Abstract: SummarySerotonin, well known for its role in depression, has been shown to modulate immune responses. Interestingly, the plasma level of serotonin is increased in symptomatic asthmatic patients and the use of anti-depressants, known to reduce serotonin levels, provokes a decrease in asthma symptoms and an increase in pulmonary function. Thus, we tested the hypothesis that serotonin affects alveolar macrophage (AM) cytokine production, altering the cytokine network in the lung and contributing to asthma pathoge… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
46
0

Year Published

2010
2010
2021
2021

Publication Types

Select...
4
4
1

Relationship

0
9

Authors

Journals

citations
Cited by 67 publications
(49 citation statements)
references
References 48 publications
3
46
0
Order By: Relevance
“…Alternatively, the presence of serum factors could modulate or synergize with 5HT, and it might have caused an overestimation of the 5HT influence. In an effort to avoid these potentially confounding issues, we have carried out all experiments on macrophages maintained in serum-free medium for 48 h. Thus, apart from the cell type-specific nature of 5HT actions, the distinct medium used for assaying 5HT might explain the discrepancy between the lack of effect of 5HT on IL-10 release seen in our experiments and those of others (20,49) and the positive action of 5HT in IL-10 production described in human alveolar cells and monocytederived dendritic cells (22,23). Despite these discrepancies, our results are in agreement with the lack of effect of 5HT 2 agonists on the LPS-induced monocyte cytokine production (21).…”
Section: Discussionmentioning
confidence: 81%
See 1 more Smart Citation
“…Alternatively, the presence of serum factors could modulate or synergize with 5HT, and it might have caused an overestimation of the 5HT influence. In an effort to avoid these potentially confounding issues, we have carried out all experiments on macrophages maintained in serum-free medium for 48 h. Thus, apart from the cell type-specific nature of 5HT actions, the distinct medium used for assaying 5HT might explain the discrepancy between the lack of effect of 5HT on IL-10 release seen in our experiments and those of others (20,49) and the positive action of 5HT in IL-10 production described in human alveolar cells and monocytederived dendritic cells (22,23). Despite these discrepancies, our results are in agreement with the lack of effect of 5HT 2 agonists on the LPS-induced monocyte cytokine production (21).…”
Section: Discussionmentioning
confidence: 81%
“…Physiologic concentrations of 5HT suppress IFN-g-induced MHC class II expression and phagocytosis in murine macrophages (17,18) and inhibit the LPS-induced IL-1b, IL-6, IL-8, IL-12p40, and TNF-a production by human monocytes and PBMCs (19)(20)(21). In human alveolar macrophages, serotonin inhibits IL-12 and TNF-a release, but it increases IL-10, NO, and PGE 2 production via 5HT 2 receptors (22). In the case of dendritic cells, 5HT impairs GM-CSF/IL-4-driven human monocyte-derived dendritic cell (MDDC) differentiation by reducing costimulatory molecule and CD1a expression as well as MLR stimulatory activity while increasing CD14 levels (23) and IL-10 production through 5HT 1 or 5HT 7 receptors (23).…”
mentioning
confidence: 99%
“…More recently Seidel et al suggested that the inflammation might be triggered by stimulation of 5HT 3 receptor subtypes with consecutive overexpression of PGE 2 [42] and it is well known that PGE 2 regulate angiogenesis in inflammatory granulation tissue [43][44][45][46][47]. Also it has been reported that the production of TNFα is inhibited in immune cells by serotonin [30,[48][49][50], and serotonin-stimulated PGE 2 release inhibits TNFα release [51,52]. Interestingly, TNFα has been shown to have paradoxical effects in Fig.…”
Section: Discussionmentioning
confidence: 98%
“…It is shown that 5-HT is responsible for the reduction of Th1 type cytokine in alveolar macrophages through the production of prostaglandin E2, which is suggested to be a contributing factor for the autoimmunity in asthma (Menard et al, 2007). Under such circumstances, it is likely that high 5-HT reduces the number of Th1 type cytokine, leading to an imbalance of Th1/Th2 subsets and amplification Th2 inflammation, possibly resulting in autoimmunity as in autism, where antibodies against brain specific proteins are identified (Cohly and Panja, 2005).…”
Section: Hyperserotonemia and Autoimmunitymentioning
confidence: 98%